A new BODIPY-based fluorescent "turn-on" probe for highly selective and rapid detection of mercury ions. Issue 49 (5th December 2018) - Zhou, Baocheng; Qin, Siyao; Chen, Bo; Han, Yifeng
Graphical abstract: Highlights: A new BODIPY-based fluorescent sensor for Hg 2+ has been designed and synthesized. The probe is highly selective for Hg 2+ over relevant competing metal ions. The probe features rapid detection kinetics (<30 s). Abstract: A new fluorescent sensor based on the BODIPY fluorophore and the carboxyl-thiol metal bonding receptor for Hg 2+ was designed and synthesized. The sensor is highly selective for Hg 2+ (about 630-fold fluorescence enhancement) over relevant competing metal ions, sensitive to ppb levels of Hg 2+ (with detection limit of 5.7 nM), and fast response toward Hg 2+ (within 30 s) in aqueous solution.